2017
DOI: 10.21608/epx.2018.8946
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction among medical students of Sohag University, Egypt

Abstract: The high prevalence of IA among medical students in Sohag University (47.7%) is a matter of concern. Identification of factors significantly associated with IA can help in the planning of comprehensive programs to raise public awareness about the hazards and determinants of IA targeting the high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
2
19
5
Order By: Relevance
“…Another possible explanation may be time differences between past and present studies, due to the accessibility of social media sites like Viber, Twitter, TikTok, and Instagram, which are the main reasons people use the Internet [ 40 ]. However, the finding of the current study was lower than those of studies done in Egypt (47.7%) [ 25 ], Saudi Arabia (31.7%) [ 16 ], China (26.7%) [ 13 ], Nepal (42%) [ 17 ], and Greece (32.2%) [ 41 ]. This difference could be attributable to the longitudinal study design used in the United States.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Another possible explanation may be time differences between past and present studies, due to the accessibility of social media sites like Viber, Twitter, TikTok, and Instagram, which are the main reasons people use the Internet [ 40 ]. However, the finding of the current study was lower than those of studies done in Egypt (47.7%) [ 25 ], Saudi Arabia (31.7%) [ 16 ], China (26.7%) [ 13 ], Nepal (42%) [ 17 ], and Greece (32.2%) [ 41 ]. This difference could be attributable to the longitudinal study design used in the United States.…”
Section: Discussioncontrasting
confidence: 86%
“…In the present study, the prevalence of problematic Internet use was found to be 1.69 times higher in males than in females [AOR = 1.69, 95% CI: 1.12, 2.56]. This result is supported by studies carried out in Egypt [ 25 ] and Iran [ 37 ]. The possible justification for this strong association could be explained by the fact that males are more likely than females to have a high level of web familiarity and also the fact that men receive less parental supervision and they use the Internet for entertainment purposes more than women [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Severe Internet dependency was 0.2% in Greek medical students [28]. Internet addiction in medical students in a previous study was 47.7% [29], a result higher than that seen in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…Prevalence of IA is 47% according to the results of a previous study conducted in Sohag Governorate among medical students in Sohag University (Ali et al 2017 ) and with a precision of 5% and 95% confidence interval, 1.00 design effect, and power of study 0.8; a minimum sample size estimated was 380 subjects. The total sample size was 746: 373 students from faculty of medicine and 373 non-medical students from faculty of science.…”
Section: Participants and Methodsmentioning
confidence: 99%